Lag for Public Access to the Minutes of Executive Board Meetings. (Policy Papers; Policy Paper, 2014)
At the recent Review of the Fund's Transparency Policy on June 24, 2013, the Executive Board agreed to further consider options to reduce the time lag for public access to Executive Board meeting minutes under the Open Archives Policy. Although a majority of Executive Directors saw scope for reducing the time lag for public access to Board meeting minutes from five years to three years, a significant minority of Directors favored maintaining the existing lag in order to strike a balance between informing the public about the Board's views and maintaining the candor of Board discussions. The Board requested that staff undertake further analysis of the issue. Accordingly, this paper provides a more detailed assessment of the current practice and a discussion of the potential costs and benefits of possible options for further reform.